Beyond the energy transition: mapping the emerging field of energy communication - Höhs, Florentina (Frontiers in Communication, 2026)
The escalating climate crisis has made the renewable energy transition a must. Yet, communicative efforts often show limited connection to local contexts, hindering the full adoption of sustainable energy solutions. Despite its critical role, energy communication remains underexplored in academia. This study addresses that gap by exploring the interdisciplinary field of energy communication, focusing on how different research disciplines approach, study, and, thus, contribute to a better understanding of communicating (in) the energy transition. This semi-systematic literature review examines 69 peer-reviewed articles on formal (e.g., disciplinary backgrounds) and thematic attributes, such as the role of communication. Findings highlight the field's interdisciplinarity, diverse conceptualizations of communication, a certain narrowness in terms of the communicators and channels analyzed, not acknowledged actor interconnections, and the often-missed relevance of local acceptance. The review provides an overview of the current discourse, aiming to improve the critical theorizing and understanding of renewable energy issues.